2006
DOI: 10.1007/s11148-006-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Aluminosilicate ores processed by a fluoride method

Abstract: An innovative method for preparation of mullite-based refractories from aluminosilicate topaz ores is proposed in which the mineral ore is treated with ammonium fluoride; the excess silicon dioxide is removed in the form of gaseous ammonium hexafluorosilicate. The desiliconized mixture is sintered to obtain a lightweight mullite refractory with a fibrous structure.Mullite composed of 72% Al 2 O 3 and 28% SiO 2 finds ever-increasing application in high-temperature technologies; mullite-based ceramics display lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…(3) (NH4)3SiF7 → (NH4)2SiF6 + HF↑ + NH3↑ (4) Solid-phase sintering of ilmenites, scheelite, wolframite, non-bauxite ores (kaolins, high-alumina shales, anorthosites, alkaline aluminosilicates etc.) with NH4HF2 or NH4F revealed that the fluorating agent is in molten state [12][13][14][15][16]. We also found that mixing and grinding at room temperature lead to intensive wetting of the reaction mixture due to the formation of ammonia and water.…”
Section: Results and Dscussionmentioning
confidence: 75%
See 1 more Smart Citation
“…(3) (NH4)3SiF7 → (NH4)2SiF6 + HF↑ + NH3↑ (4) Solid-phase sintering of ilmenites, scheelite, wolframite, non-bauxite ores (kaolins, high-alumina shales, anorthosites, alkaline aluminosilicates etc.) with NH4HF2 or NH4F revealed that the fluorating agent is in molten state [12][13][14][15][16]. We also found that mixing and grinding at room temperature lead to intensive wetting of the reaction mixture due to the formation of ammonia and water.…”
Section: Results and Dscussionmentioning
confidence: 75%
“…The separation of tailing components during hydrochemical interaction with ammonium bifluoride in solution is based on the formation of fluorine-containing compounds having various physicochemical properties. The thermodynamic simulation showed that fluorination reactions of silicon-containing oxide phases and most of minerals begin at temperatures below 200 °С and are accompanied by heat release [12][13][14]. The interaction of NH4HF2 with the basic mineral pyroxene CaMgSi2O6 to form poorly soluble and highly soluble simple and complex fluorides is possible under standard conditions according to eq.…”
Section: Results and Dscussionmentioning
confidence: 99%
“…In recent years, a simple, effective, and comparatively safe dissolution method with the use of ammonium fluorides (NH 4 HF 2 or NH 4 F) shows great potential for the digestion of geological samples. NH 4 HF 2 was used in innovative method for preparation of mullitebased refractories from aluminosilicate quartz-topaz ores [2] or for the synthesis of mullite from kaolin [3]. A new technique of decomposing beryl ore [4] or a treatment of gold-containing graphite-bearing ores with NH 4 HF 2 to concentrate gold [5] was recently suggested.…”
Section: Introductionmentioning
confidence: 99%